2016
DOI: 10.1038/srep29483
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone accumulation as a function of stress evidences adaptation to high hydrostatic pressure in the piezophilic archaeon Thermococcus barophilus

Abstract: The accumulation of mannosyl-glycerate (MG), the salinity stress response osmolyte of Thermococcales, was investigated as a function of hydrostatic pressure in Thermococcus barophilus strain MP, a hyperthermophilic, piezophilic archaeon isolated from the Snake Pit site (MAR), which grows optimally at 40 MPa. Strain MP accumulated MG primarily in response to salinity stress, but in contrast to other Thermococcales, MG was also accumulated in response to thermal stress. MG accumulation peaked for combined stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 64 publications
2
28
0
3
Order By: Relevance
“…Consistent with this hypothesis, T. barophilus cells were shown to express stress proteins at ambient pressure57. This view is further supported by the piezophysiology study of Cario et al 58. which clearly shows that under low pressure conditions, T. barophilus cells accumulate the small organic osmolyte, mannosyl-glycerate (MG).…”
Section: Discussionmentioning
confidence: 52%
“…Consistent with this hypothesis, T. barophilus cells were shown to express stress proteins at ambient pressure57. This view is further supported by the piezophysiology study of Cario et al 58. which clearly shows that under low pressure conditions, T. barophilus cells accumulate the small organic osmolyte, mannosyl-glycerate (MG).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, stress-induced denaturation of proteins can be counteracted by the chaperonin's support of correct refolding. [1][2][3][4] Here, we investigated the effect of temperature and pressure stress on the conformational stability of the heat shock protein (Hsp) complex GroEL-GroES of Escherichia coli (Fig. 1a), which belongs to the group I chaperonins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of high hydrostatic pressure on growth and metabolism is less frequently investigated due to the difficulties involved in the experimental design (Takai et al, 2008). For example, previous studies of piezophilic micro-organisms have suggested that energy production and central metabolism-related genes appear to be overexpressed under high hydrostatic pressures (Amrani et al, 2014;Cario, Jebbar, Thiel, Kervarec, & Oger, 2016;Michoud & Jebbar, 2016;Pradel et al, 2013;Vannier, Michoud, Oger, Marteinsson, & Jebbar, 2015). A recent study involving high-pressure culturing of a piezophilic and chemolithoautotrophic epsilonproteobacterium (Nautilia sp.…”
mentioning
confidence: 99%